2017
DOI: 10.1016/j.jesf.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exercises on left ventricular systolic and diastolic heart function in sedentary women: Step-aerobic vs core exercises

Abstract: The purpose of this study is to investigate the effect of 16 weeks step-aerobic exercises and core exercises on left ventricular structure and function with some physiological parameters in sedentary women.MethodsTo achieve the purpose of this study, a total of 45 volunteers including (step-aerobic group (SAG, n = 25), core exercise group (CEG, n = 20) were selected as participants. Two different exercises were applied for 4 days a week, throughout 16 weeks, within 60 minutes for each exercise with the intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 57 publications
1
7
1
Order By: Relevance
“…The first finding of this study is that the spinning exercise program significantly decreased body weight, BMI, fat %, waist and hip circumference parameters in the experimental group (Table 2). Previous studies [27][28][29][30] reported that regular aerobic and strength exercises positively influenced physical and anthropometric parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The first finding of this study is that the spinning exercise program significantly decreased body weight, BMI, fat %, waist and hip circumference parameters in the experimental group (Table 2). Previous studies [27][28][29][30] reported that regular aerobic and strength exercises positively influenced physical and anthropometric parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Step-aerobic exercises cause a significant decrease in body weight, body mass index, waist area and hip circumference of women (Cicek, et al, 2017). The application of Step-aerobic exercises positively affects the health of women aged 20-35 years (Masliak, 2015).…”
Section: Pilates Andmentioning
confidence: 99%
“…Step training, also known as step aerobics, is an aerobic exercise that can improve cardiorespiratory fitness [ 16 ], was popularized by US aerobics competitor Gin Miller in the 1990s. Step training programs are widely implemented in gyms, combining music rhythms and resistant exercises in a variety of exercises [ 17 ].…”
Section: Introductionmentioning
confidence: 99%